Accelerated placental aging in early onset preeclampsia pregnancies identified by DNA methylation. (March 2017) - Mayne, Benjamin T; Leemaqz, Shalem Y; Smith, Alicia K; Breen, James; Roberts, Claire T; Bianco-Miotto, Tina
Aim: To determine whether dynamic DNA methylation changes in the human placenta can be used to predict gestational age.Materials & methods: Publicly available placental DNA methylation data from 12 studies, together with our own dataset, using Illumina Infinium Human Methylation BeadChip arrays.Results & conclusion: We developed an accurate tool for predicting gestational age of placentas using 62 CpG sites. There was a higher predicted gestational age for placentas from early onset preeclampsia cases, but not term preeclampsia, compared with their chronological age. Therefore, early onset preeclampsia is associated with placental aging. Gestational age acceleration prediction from DNA methylation array data may provide insight into the molecular mechanisms of pregnancy disorders.